National Policy on China One Belt-One Road (OBOR) Initiative Towards Indonesia as Global Maritime Nexus - Riko Ratna Setiawan; Muhammad Kamil (Sospol : Jurnal Sosial Politik, 2021)
One Belt-One Road Initiative is a huge project that is still a subject of discussion in the world. The project initiated by the Chinese state invites cooperation with various countries in the world in order to reactivate the maritime silk route, including Indonesia. There are 5 pillars of OBOR which are strengthening connectivity, improving infrastructure, promoting trade and scurity, increasing monetary circulation and increasing public understanding of maritime cooperation. There are some indonesian political experts argue that this cooperation will be dominated by China in all five pillars, which in the end will only make Indonesia “an instrument", not an actor. This is what the authors will discuss in this research. The purpose of this research is to see how the national policy prospects on OBOR regulations. This research is analyzed using descriptive qualitative methods by taking data from various relevant sources to the discussion topic. This research has a result that there are several national policies that can be implemented by Indonesia to strengthen its position as an actor in OBOR, where Indonesia should to provide escort to their national interests in the OBOR project.